An environmental assessment of water replenishment to a floodplain lake. (1st November 2017) - Lóczy, Dénes; Dezső, József; Czigány, Szabolcs; Prokos, Hedvig; Tóth, Gabriella
Abstract: There are numerous wetland rehabilitation projects worldwide, but their efficiency is seldom assessed comprehensively. Oxbow lakes are wetlands of particular sensitivity. Within a large-scale floodplain rehabilitation project in Hungary, the Old Drava Programme, water replenishment was first carried out for the Cún-Szaporca oxbow lakes, a key area in the project. To assess its sustainability, the entire hydrological system has been monitored. From the data of hydrological monitoring (infiltration, soil moisture, groundwater/lakewater interaction) it is claimed that water replenishment involves significant losses through seepage (4.1 and 1.46 mm d −1 ) and evaporation (3.01 and 1.44 mm d −1 ) in the studied pre-intervention and replenishment periods, resp. Infiltration alone is insufficient to replenish groundwater and raise oxbow lake levels. In the critical summer half-year evaporation is intensive in the neighbouring agricultural fields. Groundwater table dynamics are controlled by hyporheic and groundwater flow. Major impact on the water balance of the oxbow lakes is exerted by the regime of the Drava River. A deepened lakebed is recommended to ensure more effective water retention in the oxbow lake. From the local study conclusions are drawn for the feasibility of rehabilitation at floodplain scale and in areas with similar hydromorphological conditions. Graphical abstract: Highlights: Water scarcity makes floodplain rehabilitation necessary. Out of the four water inputs the Drava river regime is the most important. River incision mostly prevents direct water inflow to oxbow lake from the Drava. Monitoring revealed substantial losses of water replenished from a tributary.